Invisibilized creativity: Sociogenesis of an “innovation” process developed by cartoneros for post-consumption waste recycling - Carenzo, Sebastian (2017)
Unlike the private companies that runs the waste collection systemthe recovery and classification of waste carried out by cartoneros (waste pickers) in Buenos Aires metropolis has not yet been acknowledged as a “public service” (one of the main demands of cartonero organizations). Their work is based on the commercialization of recovered materials for the local and global recycling industry in a market defined by high levels of intermediation and incidence of monopolies in price formation. Consequently, levels of profitability attained in this first link of the chain are extremely meager, hence the importance of achieve value-adding issues becomes key for strengthen the economies of their organizations. Moreover, some public policy actions were oriented to address this goal by a so called process of "technification" of their working process. However, the results obtained so far, were not encouraging at all. Over more than a decade of the emergence of the cartonero phenomenon in Argentina, the technological features of their job have not shown significant changes. Most of them still focus on collecting and sorting as main activities, using very rudimentary tools and machines and obtaining a small profit if we consider the hard work they make on a daily basis. Departing from an ethnographic approach this article reconstructsand analyzes an “innovation” process developed by members of a cartonero cooperative in the Greater Buenos Aires. The project involves the recycling of industrial cellulose waste for manufacturing bricks and plates for housing construction. The core of myargument can be synthesized in the following question: what happens when an “innovation” process does not come from the contribution of specialized “technicians”, but responds to an experimental practice developed by the cartoneros themselves?.This shift at the level of the socially legitimate locus to produce “innovation” is analytically revealing for examining the contradictory dynamics in the construction of social relations deployed in this experience, focusing mainly on the tensions present in the institutionalization of the ongoing creative process.